2012
DOI: 10.1111/j.1747-0803.2012.00668.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Oral and Intravenous Ibuprofen for Medical Closure of Patent Ductus Arteriosus: Which One Is Better?

Abstract: Oral ibuprofen therapy is as efficacious as intravenous ibuprofen with some concerns about increased sepsis and bronchopulmonary dysplasia incidence. However, comprehensive and large-scale pharmacokinetic studies are required in order to prove this efficacy. On the other hand, intravenous ibuprofen still remains to be the drug of choice for patent ductus arteriosus but only with meticulous control of serum sodium levels in smaller infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 37 publications
0
10
1
1
Order By: Relevance
“…Several previous studies, including 1 systematic review and meta-analysis, have shown that oral ibuprofen is as effective as intravenous ibuprofen and has fewer side effects. [1823] Further, 1 trial has specifically shown that oral ibuprofen is more effective than intravenous ibuprofen for ductal closure in VLBW infants. [24] In the long run, preterm infants who were treated with oral ibuprofen for PDA had similar neurological, neurosensory, and cognitive outcomes at 2 years of age to patients who received intravenous ibuprofen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies, including 1 systematic review and meta-analysis, have shown that oral ibuprofen is as effective as intravenous ibuprofen and has fewer side effects. [1823] Further, 1 trial has specifically shown that oral ibuprofen is more effective than intravenous ibuprofen for ductal closure in VLBW infants. [24] In the long run, preterm infants who were treated with oral ibuprofen for PDA had similar neurological, neurosensory, and cognitive outcomes at 2 years of age to patients who received intravenous ibuprofen.…”
Section: Discussionmentioning
confidence: 99%
“…[21] On the other hand, at least 1 study raised concerns about increased sepsis and bronchopulmonary dysplasia incidence with oral ibuprofen as compared to intravenous ibuprofen. [23] However, the evidence overall supports the use of oral ibuprofen as a safe and effective alternative agent for the treatment of PDA in neonates.…”
Section: Discussionmentioning
confidence: 99%
“…Considering observational studies, all 24 studies had a cohort design. Based on the Newcastle-Ottawa Quality Assessment Scale for this type of study design, 12 studies obtained a score of 9 out of [79-81, 84, 89, 91, 93-95, 97, 99, 101], nine had a score of [83,85,86,88,92,96,98,100,102], two studies a score of 7 [82,87], and one a score of 6 [90] (Appendix 6).…”
Section: Risk Of Biasmentioning
confidence: 99%
“…Her iki ilacın da gastrointestinal sistem ve renal sistem üzerinde yan etkileri olabilmektedir (3)(4)(5)(6). İntravenöz ibuprofen pahalı olması ve çoğu yerde bulunamaması nedeniyle oral ibuprofen tercih edilmektedir (7,8). Son yıllarda intravenöz veya oral parasetamolun de PDA'nın medikal kapatma tedavisinde etkin olduğunu bildiren çalışmalar bildirilmiştir (9)(10)(11).…”
Section: Introductionunclassified